Mentorship in EMWA: A perspective. (1st June 2013) - Salita, Joselita T
Abstract : Mentorship is a relationship practised in many fields of endeavour, including business, and has been recognised to be an important driving force in enhancing career development and professional satisfaction for both mentors and mentees. The importance and necessity of mentorship in EMWA are discussed not only at the level of professional development but also at the ethical level such as promoting and guarding responsible medical writing. Issues which have to be considered in carrying out a mentoring scheme and how to tackle them are also discussed.